2018
DOI: 10.22452/ajba.vol11no1.1
|View full text |Cite
|
Sign up to set email alerts
|

Do Shariah-compliant Companies Engage Lesser Earnings Management Behaviour?

Abstract: Manuscript type: Research paper. Research aims: This study aims to understand how reputation, financial distress and financial performance influence Shariah-compliant companies into engaging earnings management behaviour. The financial data of 69 FTSE Bursa Malaysia 100 Index companies, dating 2010 to 2014 (five years), were analysed. Design/ Methodology/ Approach: This study uses the Modified Jones model (Jones, 1991; Dechow, Sloan, & Sweeney, 1996), Roychowdhury's model (2006) to examine earnings management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…However, from the 76% of SCC, only those that are listed in the FTSE Bursa Malaysia 100 Index were part of the target sample as the companies are ranked by market capitalization. This was consistent with the prior study by Sabrun, Muhamad, Yusoff, and Darus (2018) on SCC that examined the performances and study of accounting conservatism by .…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…However, from the 76% of SCC, only those that are listed in the FTSE Bursa Malaysia 100 Index were part of the target sample as the companies are ranked by market capitalization. This was consistent with the prior study by Sabrun, Muhamad, Yusoff, and Darus (2018) on SCC that examined the performances and study of accounting conservatism by .…”
Section: Methodssupporting
confidence: 91%
“…To ensure consistency for the companies' categorization, one of the criteria was that a company was classified as Shariah-compliant if the company was listed as Shariah-compliant companies throughout the period of 2012 to 2017. From the 100 Index, 17 companies from the financial services sector were excluded because the measurement of the sector is complex and treated differently (Grougiou, Leventis, Dedoulis, & Owusu-Ansah, 2014;Sabrun et al, 2018). Following ; Sabrun et al (2018) and Wan et al (2015) that only use the same financial year-end, out of 83 companies, only 39 companies announced their financial year end on 31 December, the other 44 companies have different year-end such as March, June, July, August and September.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wan Ismail et al (2015) concluded that Sharia was an effective monitoring mechanism in reducing opportunistic managerial behavior through accrual quality in Malaysia. In contrast, Sabrun, Muhamad, Yusoff, and Darus (2018) suggested a different result. They found that Sharia-obedient firms might not exercise the Islamic ethical conducts thoroughly.…”
Section: Introductionmentioning
confidence: 91%
“…[7] study the effects of financing policy and countries' institutionalfinancial characteristics on earnings management practices in Latin American companies. [8] aim to understand how reputation, financial distress and financial performance influence Shariah-compliant companies into engaging earnings management behaviour. [9] analyze various points of view of the role of the Bulgarian leader and his/her efficiency in the accomplishment of earnings objectives of the enterprises in the Bulgarian and world reality and guidelines for its sustainability and successful application in contemporary economics.…”
Section: Literature Reviewmentioning
confidence: 99%